Treat the "Untreatable" by a Photothermal Agent: Triggering Heat and Immunological Responses for Rabies Virus Inactivation. Issue 2 (17th November 2022) - Bai, Yujie; Huang, Pei; Feng, Na; Li, Yuanyuan; Huang, Jingbo; Jin, Hongli; Zhang, Mengyao; Sun, Jingxuan; Li, Nan; Zhang, Haili; Xia, Xianzhu; Tang, Ben Zhong; et al.
Abstract: Rabies is a fatal neurological zoonotic disease caused by the rabies virus (RABV), and the approved post‐exposure prophylaxis (PEP) procedure remains unavailable in areas with inadequate medical systems. Although strategies have been proposed for PEP and postinfection treatment (PIT), because of the complexity of the treatment procedures and the limited curative outcome, developing an effective treatment strategy remains a holy grail in rabies research. Herein, a facile approach is proposed involving photothermal therapy (PTT) and photothermally triggered immunological effects to realize effective PEP and PIT simultaneously. The designed photothermal agent (N + TT‐ m CB nanoparticles) featured positively charged functional groups and high photo‐to‐heat efficiency, which are favorable for virus targeting and inactivation. The level of the virus at the site of infection in mice is significantly decreased upon treatment with orthotopic PTT, and the transfer of the virus to the brain is significantly inhibited. Furthermore, the survival ratio of the mice three days postinfection is increased by intracranial injection of N + TT‐ m CB and laser irradiation. Overall, this work provides a platform for the effective treatment of RABV and opens a new avenue for future antiviral studies. Abstract : A facile approach that treats the untreatable rabies virus based on a photothermal agent is designed involving high photo‐to‐heat efficiency and positively charged functional groups. The virus is inactivated by photothermal therapy and photothermally triggered immunological effects which can realize effective post‐exposure prophylaxis and postinfection treatment simultaneously.